2006
DOI: 10.1007/s10661-006-7674-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Metals Concentrations of Water, Sediment and Hyalella Azteca from Lakes in the Vicinity of the Sudbury Metal Smelters, Ontario, Canada

Abstract: Hyalella azteca (Crustacea: Amphipoda), water and sediments from 12 circum-neutral lakes between Sudbury and North Bay in Ontario, Canada were sampled in August 1998 and analyzed for 10 metals including Cu, Zn, Cd, Ni, Pb, Co, Mo, V, Ba and Ti. Statistical analyses showed that concentrations of the metals in H. azteca, water and sediment differed significantly (ANOVA, P < 0.05) among lakes (except for Zn and Pb in H. azteca and Mo in water). There was a trend of declining metal concentration, especially for Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…The EC values of the lake water were found to be lower as compared to the maximum permissible levels recommended by WHO (2004) guidelines for drinking water. The mean conductivity values of the lake water were lower than those reported in literature (Table 1) for other lakes [21][22][23]31] except in the case of Tuskegee Lake, USA [30]. Mean TDS, TSS and TS values in the present study were found to be 124.5, 621.4 and 745.8 mg/L respectively.…”
Section: -contrasting
confidence: 84%
See 2 more Smart Citations
“…The EC values of the lake water were found to be lower as compared to the maximum permissible levels recommended by WHO (2004) guidelines for drinking water. The mean conductivity values of the lake water were lower than those reported in literature (Table 1) for other lakes [21][22][23]31] except in the case of Tuskegee Lake, USA [30]. Mean TDS, TSS and TS values in the present study were found to be 124.5, 621.4 and 745.8 mg/L respectively.…”
Section: -contrasting
confidence: 84%
“…It has been reported that the elevated concentrations of Cd can cause nausea, vomiting, salivation and renal failure as well as kidney, liver and blood damages [46]. The concentration of Pb in the understudy lake water was higher than other 8 lakes water samples [23,24,26,27,[29][30][31][32] but significantly lower than those reported in the literature [21,28]. The adverse health effects of lead consist of various cancers, adverse reproductive outcomes, cardiovascular and neurological diseases [47].…”
Section: -mentioning
confidence: 86%
See 1 more Smart Citation
“…Much research has been done in different metal mines and surroundings on the release and accumulation (Yang et al 2006;Shuhaimi-Othman et al 2006), transportation and transformation (Zhu et al 2005), spatial distribution and bioavailability of the heavy metals (Zhang et al 2004;Sun et al 2008), as well as the potential environmental risks of heavy metals (Hu et al 2006;Fan et al 2007). Total heavy metal concentration is an important indicator of pollution risks.…”
Section: Introductionmentioning
confidence: 99%
“…Toxic level of Pb in human body is 500 ppm beyond which it causes anaemia, brain damage and vomiting 16 . Further, Shuhaimi-Othmnan 18 noted that the adverse effects of Pb consist of manifestation of cancers, adverse reproductive outcomes, cardiovascular and neurological diseases. The concentrations of Pb in this study ranged from 0.01-1.0 mg/L with a mean value of 0.01±0.02 mg/L.…”
Section: Trace Metal Analysismentioning
confidence: 99%